PEMANFAATAN PEKARANGAN UNTUK BUDIDAYA ANGGUR DENGAN MEDIA CAMPURAN BIOCHAR - Susila Herlambang; Danang Yudhiantoro; Astrid Wahyu Adventri Wibowo (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic has significant socio-economic impacts for all regions in Indonesia, one of which is in Bantul Regency. In anticipation of this impact, Mayungan Hamlet government officials and the community service team made several programs related to the development of grape cultivation in their home yard. With this activity, it is hoped that the community will be able to improve the family economy which was originally declining. The series of activities carried out were mapping of village potentials, outreach, practice, mentoring, and technical guidance. This activity was chosen in order to make it easier for the community to accept new technology with the formulation of planting media made from compost and coconut shell biochar. The obstacle faced during the service was that all activities were carried out during a pandemic where there were restrictions on community activities so that not all participated in this activity. However, all activities were successfully carried out, as evidenced by the 14 invited community representatives, all of whom were present in every activity and there was an increase in community (cognitive) knowledge about grape cultivation.